Analyzing Coherence and Cohesion in Eleventh Graders’ Descriptive Paragraphs at SMA N 1 Sawan - Dewi, Ni Kadek Kasandra; Adnyani, Ni Luh Putu Sri; Ramendra, Dewa Putu (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study aimed to analyze how eleventh-grade students of SMA Negeri 1 Sawan in the 2024/2025 academic year construct coherent paragraphs and how they apply cohesive devices in their writing. This study employed a mixed-methods approach, which combines qualitative and quantitative descriptive techniques. Data collection was carried out through the documentation of 22 paragraphs written by students, but only 20 of these paragraphs met the analysis criteria. The main instruments in this study were the coherence assessment rubric and the cohesion frequency table. According to the findings of this study, 90% of the paragraphs were found to be coherent, with an average coherence score of 84.35%. However, 10% did not have adequate coherence. The most frequently used cohesive devices included references, substitutions, ellipsis, conjunctions, and lexical cohesion, with references and conjunctions being the most prevalent. These findings highlight the importance of targeted teaching strategies in enhancing students' writing competence, particularly in developing logical flow and sentence connectivity within an academic context. Therefore, this study concludes that although most students can construct coherent and cohesive descriptive paragraphs, there is still a need for improvement in the application and variation of cohesive devices.